The Effects of Persea americana leaves on the Enzymes and Organosomatic indices of Pseudomonas aeruginosa Infect Clarias gariepinus - Etire, D.I, Ukwe, I. O. K (Journal of Medical Care Research and Review, 2021)
Enzymatic activities (AST, ALT, ALP and ACP) and organosomatic indices were examined in P. aeruginosa infected aqueous leaves extracts. 120 (one hundred and twenty) of clarias garipienus of mean weight 120±13g) were intranuscukarly injected with 1.0ml of 4.1x104cfu P. aeruginosa using 2ml injection syringe and observed for disease presence/signs. After diseases presence, they were distributed into four groups in triplicate and expose/treated via immersion with P. americana aqueous leaves extracts at 0.0ml, 1.0ml, 1.5ml and 2.0ml. Blood samples were collected before infection, after disease presence, and after day 2, 5, and 7 of treatment/exposure and taken to the laboratory to ascertain the therapeutic effects of the experimental extract on infected C. gariepinus. And the organosomatic indices were analysed at the 7 day of treatment to ascertain the therapeutic effects of the extract on the organs of the infected C. gariepinus. The results shows that all the analysed enzymes (AST, ALT, ALP and ACP) were higher (P<0.05) in C. gariepinus after the infection compared to the activities before infection. The activities after day 2, 5 and 7 of the treatment shows that enzymes activities in the treated fish (1.0ml – 2.0ml of extracts) reduced (P<0.05) compared to the untreated (0.0ml). The organosomatic indicies assessment shows that hepatosomatic index (HSI), vescerasomatic index (VSI), spleenosomatic index (SSI) and intraperitoneal fat (FI) were higher (P>0.05) in the untreated (0.0ml) fish compared to the treated (1.0 – 2.0ml of experimental extract) fish. While the cardiosomatic index (CSI) was significantly the same across the treatments. Keywords: Aquaculture, Enzymatic changes, P. aeruginosa, Organosomatic indices, P. americana, C. gariepinus